Penerapan Sistem Informasi Manajemen untuk Pembuatan Jadwal Induk Produksi dengan Metode Linier Programming - Lailis Syafaah (Jurnal Teknik Industri, 2003)
Generally, factories always want to give bidden to consumer, therefore ne€d the best production of plain and schedule by programming linier method in order that can be eff€ctive and efficient. Reality main problem flom PT. Serasa Puma Cipta Sidoarjo was pile up of sort ploduct and little others product to next times and to threaten to the first skipsi about difficulty of factories to make QS program for actuality production ofexcellent schedule. Therefore how to actuality management of information system in ordsr that process prepamtion data in tll€ factories was not difficultly for the actuality. The meaning for based on and experienc€ last time, the factories to do that program was difficultly to program operation so production of excellent schedule realize difiiculty. To that answer need actually Management of information system for production of excellent schedule to every group product to every period.